ChemInform Abstract: The Amide C—N Bond of Isatins as the Directing Group and the Internal Oxidant in Ru‐Catalyzed C—H Activation and Annulation Reactions: Access to 8‐Amido Isocoumarins. Issue 50 (November 2016) - Kaishap, Partha Pratim; Sarma, Bipul; Gogoi, Sanjib
Abstract: A broad spectrum of target compounds is available following the 3‐component protocol shown (mechanism).